Effects of the “Spinomed active” orthosis on chronic back pain in kyphotic women with osteoporotic vertebral fractures three months and older: A randomized controlled study - Hettchen, Matthias; Willert, Sebastian; von Stengel, Simon; Kohl, Matthias; Kemmler, Wolfgang (Frontiers in Pain Research, 2022)
Vertebral fractures are frequent clinical consequences of osteoporosis. Considering the demographic change in Europe the number of vertebral fractures will quite likely increase during the next decades. Apart from pharmaceutic agents and physiotherapy, spinal orthoses are established elements of conservative therapy for vertebral (body) fractures. Recent studies on acute vertebral fractures reported positive effects on back pain, kyphosis and functional disabilities, but the efficacy of active strengthening spinal orthoses in vertebral fractures ≥6 months remains to be established. Eighty hyperkyphotic, community-dwelling women ≥65 years with chronic back pain and vertebral fractures occurred ≥3 months ago were randomly allocated to a group that wore the “Spinomed active” orthoses 2x2-3h/d for 16 weeks (SOG: n=40) or an untreated control group (CG: n=40). Study outcomes were back pain intensity, kyphosis angle, trunk strength, back pain induced- and general function and disability, functional ability (chair-rise test) and respiratory function. We applied an intention-to-treat analysis; data was consistently adjusted for baseline values applying an ANCOVA. Observing a compliance of 8214% with the wearing protocol, we determined large and significant favorable effects for back pain (p=.008), back pain-induced physical disability (p<.001) and kyphosis angle (p<.001). We also demonstrated positive effects on trunk strength (p=.049), functional ability (p=.062) and general function and disability (p=.057), although not all parameters reach significance. No relevant changes were observed for respiratory function. After a few further individual adjustments of the orthosis (n=2), no adverse effects were reported. In summary, the present study provided evidence for the efficacy of an active strengthening spinal orthoses (“Spinomed active”) in people with vertebral fractures ≥6 months. Based on our results, we recommend expanding the application of the "Spinomed active" orthosis which previously was validated for acute vertebral fractures, also to older hyperkyphotic women with osteoporotic vertebral fractures ≥3 months.